Effects of false-start disqualification rules on response-times of elite-standard sprinters - Brosnan, K. C.; Hayes, K.; Harrison, A. J. (Journal of Sports Sciences, 2017)
The 100 ms ruling for false start disqualification at athletic competitions governed by the International Association of Athletics Federations has been in force since the early 1990s. Throughout this period, there have been marked changes to the rules that govern the disqualification of athletes from sprint events incorporating starts from blocks. This study analysed all available World and European Championship response-time (RT) data from 1999 to 2014 to examine effects of rule changes on competition RT at major championships. The exponentially modified Gaussian distribution was used to model RT and make comparisons relative to athletes` sex, ruling periods and competition rounds. Revised RT thresholds of 115 ms and 119 ms were identified for men and women, respectively, indicating that the current 100 ms rule could result in some false starts not being detected in competitive athletics. The study proposes that when using existing International Association of Athletics Federations approved systems, the false start detection threshold should be increased and that men and women athletes should have different thresholds because of substantial evidence of a sex-based difference in RT in elite-standard athletes.